THE STUDENTS’ PERCEPTION OF THE PROFESSIONAL ENGLISH TEACHER AT MA PP NURUL HAQ BENTENG LEWO KABUPATEN SIDRAP - Alik, Bakri M.; Nanning, Nanning (Prodi Tadris Bahasa Inggris STAIN Parepare (IAIN Parepare), 2019)
Everyone has the different perception or arguments about an object around them. So as students, they also have perception about their teacher especially to the English teacher. In every school there are some categories of the teachers namely the good teacher, bad, friendly and the professional teacher. As the professional teachers they should have or mastery four competencies namely, pedagogical competence, professional, personality and social competence. This study was aimed to know about the professional English teacher and the students? perception of the professional English teacher. The objective of this research was to get the empirical data about the professional teacher and students? perception. The population of the research consisted of sixty students of the first grade, the second grade and the third grade. The sample of the research consisted of 60 students. The research method used in the research was a qualitative and quantitative method (Mix-method) by using descriptive design. The data was collected through observation and questionnaire. Based on the calculation, the result of the data analysis showed that the students? perception of the professional teacher got a good perception that it was included high category. In other words, the teacher at MA PP Nurul Haq Benteng lewo Kabupaten Sidrap was included in the professional teacher.